T model of growth and its application in systems of tumor-immunedynamics - Mohammad A. Tabatabai; Wayne M. Eby; Karan P. Singh; Sejong Bae (Mathematical Biosciences and Engineering)
In this paper we introduce a new growth model called Tgrowth model. This model is capable of representing sigmoidal growth as wellas biphasic growth. This dual capability is achieved without introducingadditional parameters. The T model is useful in modeling cellularproliferation or regression of cancer cells, stem cells, bacterial growth anddrug dose-response relationships. We recommend usage of the T growth model forthe growth of tumors as part of any system of differential equations. Use ofthis model within a system will allow more flexibility in representing thenatural rate of tumor growth. For illustration, we examine some systems oftumor-immune interaction in which the T growth rate is applied. We also applythe model to a set of tumor growth data.